2017
DOI: 10.1038/s41467-017-00966-x
|View full text |Cite
|
Sign up to set email alerts
|

Coralgal reef morphology records punctuated sea-level rise during the last deglaciation

Abstract: Coralgal reefs preserve the signatures of sea-level fluctuations over Earth’s history, in particular since the Last Glacial Maximum 20,000 years ago, and are used in this study to indicate that punctuated sea-level rise events are more common than previously observed during the last deglaciation. Recognizing the nature of past sea-level rises (i.e., gradual or stepwise) during deglaciation is critical for informing models that predict future vertical behavior of global oceans. Here we present high-resolution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Each bank was first mapped with an EM ® 710 multibeam echosounder (Kongsberg Maritime, Konsberg, Norway) before conducting, depending upon bank size and morphology, one or 2 ROV transects that generally extended from the base to the terrace of each bank. Banks surveyed in this study were described in detail in Nash (2013Nash ( , 2014, Hicks et al (2014), and Khanna et al (2017). In brief, Baker Bank is a 1.39 km 2 rectangular feature with a vertical relief of 16 m (Figure 2A).…”
Section: Bank and Transect Descriptionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Each bank was first mapped with an EM ® 710 multibeam echosounder (Kongsberg Maritime, Konsberg, Norway) before conducting, depending upon bank size and morphology, one or 2 ROV transects that generally extended from the base to the terrace of each bank. Banks surveyed in this study were described in detail in Nash (2013Nash ( , 2014, Hicks et al (2014), and Khanna et al (2017). In brief, Baker Bank is a 1.39 km 2 rectangular feature with a vertical relief of 16 m (Figure 2A).…”
Section: Bank and Transect Descriptionsmentioning
confidence: 98%
“…At mesophotic depths along the Gulf of Mexico (GOM) shelf, natural hard-bottom habitats are sparse and intermittently distributed. In the northwestern GOM, these habitats can be divided, based on their geologic origin, into 2 regions extending east and south of Matagorda Bay (Nash et al 2013): (1) Salt Diapir Banks that formed from sheets of allochthonous salt and (2) South Texas Banks (STB) that formed from relict carbonate reefs (Belopolsky and Droxler 1999, Khanna et al 2017. Biodiversity of reef-building and other structure-forming fauna on these banks differs with depth and physical structure (Rezak et al 1983, Hickerson et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Scleractinian coral reefs have a long history extending back to the Middle Triassic (242-247 million years ago) (Martindale et al, 2019). Specifically, there are numerous records of reefs in the paleo-GoM, including microbial reefs from the Upper Jurassic (164-153 Ma) (Mancini and Parcell, 2001), coral and rudist bivalve reefs from the Cretaceous (145-90 Ma) (e.g., Enos, 1974;Scott, 1984;Höfling and Scott, 2002;Hattori et al, 2019), sponge and coral reefs from the Paleocene (66 to 59 Ma) (Bryan, 1991), as well as the drowned and living reef banks that initiated during the last deglacial period (∼14,500 years ago) (Khanna et al, 2017).…”
Section: Contextualizing Anthropogenic Changes With Hot-house Climatementioning
confidence: 99%
“…3a). However, submerged coral reefs have been discovered on continental shelves and on island margins in many tropical and subtropical areas worldwide (e.g., Khanna et al, 2017;Rovere et al, 2018;Webster et al, 2004). Other reports have shown that sea-level rises since the Last Glacial Maximum have been non-linear (Fairbanks, 1989), and that reef back-stepping and reef drowning can be seen as indicators of rapid sea-level rise (e.g., Blanchon and Shaw, 1995).…”
Section: Introductionmentioning
confidence: 99%